2016
DOI: 10.1080/21568316.2016.1152290
|View full text |Cite
|
Sign up to set email alerts
|

Tourism enterprises beyond the margins: the relational practices of Aboriginal and Torres Strait Islander SMEs in remote Australia

Abstract: This exploratory article commences by noting views from the literature that in areas like remote Australia, small to mediumsized tourism enterprises operated by Indigenous people struggle with geographical distance, lack of business capabilities and other factors. These perspectives provide basis to explore remote tourism enterprise use of relational practices that "configure" external resources to improve competitiveness. The article investigates relational practices carried out by small to mediumsized touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
8
0
4
Order By: Relevance
“…Aboriginal tourism entrepreneurs draw on 60,000 years of heritage to offer unique and distinct cultural experiences to domestic and international tourists [26], and in remote regions, it is argued that these enterprises provide opportunities to empower local communities [27] and contribute to regional sustainability and economic development [28,29]. Furthermore, and in contrast to alternative studies such as Whitford [30] which mention an adhoc approach by Indigenous operators to tourism skills, knowledge and education, Jacobsen has found that Aboriginal entrepreneurs in remote regions display high levels of business acumen and success [31]. However, the benefits to Aboriginal communities and local regions that were anticipated as a result of this success have not been realised.…”
Section: Challenges and Inhibitors To Success And Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Aboriginal tourism entrepreneurs draw on 60,000 years of heritage to offer unique and distinct cultural experiences to domestic and international tourists [26], and in remote regions, it is argued that these enterprises provide opportunities to empower local communities [27] and contribute to regional sustainability and economic development [28,29]. Furthermore, and in contrast to alternative studies such as Whitford [30] which mention an adhoc approach by Indigenous operators to tourism skills, knowledge and education, Jacobsen has found that Aboriginal entrepreneurs in remote regions display high levels of business acumen and success [31]. However, the benefits to Aboriginal communities and local regions that were anticipated as a result of this success have not been realised.…”
Section: Challenges and Inhibitors To Success And Sustainabilitymentioning
confidence: 99%
“…Collaboration between stakeholders that brings together individuals and groups who can contribute different forms of capital, including the financial, and thus support the success of Aboriginal enterprises is needed instead [47]. While there are often mismatches in motives between Aboriginal entrepreneurs and external stakeholders who may have different understandings of the purposes of Aboriginal businesses, within remote regions, Jacobsen [31] has identified that high levels of cooperation between Aboriginal enterprises do tend to result in enterprise success.…”
Section: Challenges and Inhibitors To Success And Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Overview of perceptions of German wine tourism from the winery perspective (Koch, Martin, & Nash, 2013) International Journal of Wine Business Research Patterns of innovation in tourism 'Small and Medium-size Enterprises' (Tejada & Moreno, 2013) Service Industries Journal Social network enterprise behaviors and patterns in SMEs: Lessons from a Portuguese local community centered around the tourism industry (Fernandes, Belo, & Castela, 2016) The growth of micro, small, and medium-sized hotel enterprises: the hoteliers' perspectives (Carlisle et al, 2013) Arab World Geographer Tourism enterprises beyond the margins: the relational practices of Aboriginal and Torres SMEs in remote Australia (Jacobsen, 2017) Tourism Planning and Development (Corrêa, 2014) Turismo em Análise A percepção dos gestores quanto às práticas sustentáveis implantadas em meios de hospedagem de pequeno porte (Rossetto, 2014) Revista de Turismo Contemporâneo Implementação de ações inovadoras e empreendedorismo: estudo de múltiplos casos em empresas hoteleiras de pequeno porte (Sacramento & Teixeira, 2014b) Caderno Virtual de Turismo Marketing estratégico para eventos: um estudo de caso das estratégias de marketing utilizadas pela Oktoberfest de Santa Cruz do Sul, RS (Barbosa, 2013)o turismo de eventos apresenta-se como uma alternativa rent\u00e1vel para alavancar a economia e proporcionar o desenvolvimento regional de determinadas localidades. Este artigo teve como objetivo investigar as estrat\u00e9gias de marketing para eventos utilizadas pela Oktoberfest de Santa Cruz do Sul/RS, o modelo de planejamento estrat\u00e9gico para eventos utilizado foi o de Allen et al (2008…”
Section: Information Developmentunclassified
“…O agrupamento III (Figura 4) associou as atividades diversificadas, que se referem à indústria do turismo, com as categorias Inovação em Marketing e Vantagem Competitiva. A presença ou expectativa de cooperação ou outros níveis de relacionamentos interorganizacionais foram ações recorrentemente citadas nesses estudos, tendo como justificativa a capacidade de indução à competitividade (Jacobsen, 2017). Embora a Figura 4 -Mapa perceptual: categorias e trade turístico Fonte: Elaborada pelos autores com auxílio do SPSS cooperação possa ser estabelecida entre empresas pertencentes ao mesmo mercado (Jaafar et al, 2012), nem sempre os empresários, motivados pela competição, desejam cooperar com seus similares (Koch et al, 2013).…”
Section: Trade E Marketing Turísticosunclassified